2016
DOI: 10.1177/2325967116631335
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intraoperative Intra-articular Morphine and Clonidine Injection in the Acute Postoperative Period After Hip Arthroscopy

Abstract: Background:Previous authors have suggested that intra-articular morphine and clonidine injections after knee arthroscopy have demonstrated equivocal analgesic effect in comparison with bupivacaine while circumventing the issue of chondrotoxicity. There have been no studies evaluating the effect of intra-articular morphine after hip arthroscopy.Purpose:To evaluate the efficacy of intra-articular morphine in combination with clonidine on postoperative pain and narcotic consumption after hip arthroscopy surgery f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Drugs such as local anesthetics are classically known for their chondrotoxic effects while morphine may provide a less chondrotoxic option for intra‐articular analgesia …”
Section: Therapeutic Modulation Of Receptors In the Synoviummentioning
confidence: 99%
“…Drugs such as local anesthetics are classically known for their chondrotoxic effects while morphine may provide a less chondrotoxic option for intra‐articular analgesia …”
Section: Therapeutic Modulation Of Receptors In the Synoviummentioning
confidence: 99%
“…[8][9][10][11] Supplemental forms of anesthesia before, during, and after certain arthroscopic procedures have also been shown to significantly reduce opioid consumption. 12,13 Given that only 4% of patients in the study required an inpatient admission, many of these ED visits may have been preventable. By enforcing a multimodal approach to pain management and perioperative patient education surrounding narcotic use, the burden on the health care system following hip arthroscopy may be reduced further still.…”
Section: See Related Article On Page 1575mentioning
confidence: 99%
“…[ 7 8 ] In a study by Cogan et al ., the authors reported a significant decrease in the need for opioids after surgery when an intraoperative intra-articular injection of morphine and clonidine was used. [ 9 ] In another study conducted in renal transplant patients, patient-controlled analgesia morphine requirements were significantly reduced after surgery in the ERAS group versus the non-ERAS group. [ 10 ] Despite limiting opioid usage preoperatively and decreased pain scores and the need for opioids after surgery, the culture of prescribing pain medications postoperatively after discharge has remained unchanged.…”
Section: Why Use Enhanced Recovery After Surgerymentioning
confidence: 99%